PELATIHAN PENGELOLAAN ARSIP SECARA DIGITAL PADA KANTOR DESA TELUK TAMIANG KABUPATEN KOTABARU - Irawan, Agus; Risa, Mey; Permanasari, Linda (Jurnal IMPACT: Implementation and Action, 2024)
Abstract This community service activity is carried out as a multi-disciplinary scientific application, namely educational activities in the form of training and assistance in using the GMail and Google Drive applications in order to improve the skills of administrative staff regarding information technology in Teluk Tamiang Village, Kotabaru Regency. The proposed scheme is the Community Empowerment Program scheme. This service activity is problem solving in nature, namely in the form of training on administrative activity processes by utilizing information technology, especially the use of several Google Workspace facilities. The target audience (partners) are the administrative staff of Teluk Tamiang Village, Kotabaru Regency. This activity program is to improve the skills of Teluk Tamiang Village administration staff, Kotabaru Regency in storing archives/files digitally on the Google Workspace application in the Gmail accounts owned by the staff. The benefit is that these files can be shared and used together to help carry out work more quickly, effectively and efficiently. Besides that, it also functions to back up data, as well as distribute data more quickly via social media to other staff who need the data. The community service methods used include: (1) Preparation; (2) Digital archiving training starting from the practice of creating accounts, using Google Workspace media, storing and sharing data; and (3) evaluation of participants' abilities. The results obtained from this activity were: (1) Participants began to increase their understanding in managing archives/files; (2) Overall training participants can digitize archives using the Google Workspace application